Proteomic patterns predict acute graft-versus-host disease after allogeneic hematopoietic stem cell transplantation - Weissinger, Eva M.; Schiffer, Eric; Hertenstein, Bernd; Ferrara, James L.; Holler, Ernst; Stadler, Michael; Kolb, Hans-Jochem; Zander, Axel; Zürbig, Petra; Kellmann, Markus; Ganser, Arnold (Blood, 2007)
Acute graft-versus-host disease (aGvHD) contributes significantly to morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Diagnosis of GvHD is mainly based on clinical features and tissue biopsies. A noninvasive, unbiased laboratory test for GvHD diagnosis does not exist. Here we describe the application of capillary electrophoresis coupled online with mass spectrometry (CE-MS) to 13 samples from 10 patients with aGvHD of grade II or more and 50 control samples from 23 patients without GvHD. About 170 GvHD-specific polypeptides were detected and a tentatively aGvHD-specific model consisting of 31 polypeptides was chosen, allowing correct classification of 13 of 13 (sensitivity 100.0% [95% confidence interval CI 75.1 to 100.0]) aGvHD samples and 49 of 50 (specificity 98.0% [95% CI 89.3 to 99.7]) control samples of the training set. The subsequent blinded evaluation of 599 samples enabled diagnosis of aGvHD greater than grade II, even prior to clinical diagnosis, with a sensitivity of 83.1% (95% CI 73.1 to 87.9) and a specificity of 75.6% (95% CI 71.6 to 79.4). Thus, high-resolution proteome analysis represents an unbiased laboratory-based screening method, enabling diagnosis, and possibly enabling preemptive therapy.